Effect of Public Expenditure on Human Capital Development in Nigeria (2008 – 2023) - Fabian Ajijias Okwajie (IIARD International Journal of Banking and Finance Research, 2026)
The study was an examination of the effect of public expenditure on human capital development in Nigeria from 2008 to 2023. The specific objectives were to evaluate the trends and patterns of public expenditure in Nigeria from 2008 to 2023, focusing on allocations to education, health, social protection, and technology infrastructure, evaluate the Impact of Public expenditure on Education on Human capital development, five research questions and four hypotheses guided the study. The study adopted the ex-post facto research design approach with data derived from National Bureau of Statistics (NBS) and Central Bank of Nigeria (CBN) Statistical Bulletins. Descriptive statistics and Regression analysis were employed to answer the research questions and test the hypotheses @ 0. 5 level of significance. The findings of the study showed that there is significant effect of Public expenditure on Education on Human capital development ,significant effect of Public expenditure on Health on Human capital development, no significant effect of Public expenditure on Social protection on Human capital development and no significant effect of Public expenditure on Technology infrastructure on Human capital development .Recommendations proffered include the need for increase in government budgetary allocation to the education sector to enhance rapid human capital development. Also, government budgetary Allocation to the health sector should be increased while ensuring proper monitoring and evaluation of government spending on health programs implementation, The level of government spending social protection should be augmented and appropriate measures instituted to forestall misappropriation of funds in the sector so as to serve as a catalyst for human capital development. Finally, government spending on technology infrastructure should be increased so as to enhance rapid human capital development in all sectors of the economy for national development.